Un repertorio surtido: las vasijas del oasis de Laguna Blanca, Puna argentina - Scattolin, María Cristina; Bugliani, María Fabiana (Revista Española de Antropología Americana, 2005)
A collection of vessels from first millennium A.D. cemeteries located at Laguna Blanca oasis, in the southern edge of the Argentinean Puna, is examined and described. A database was created and descriptive statistics were applied; a numerical classification was also applied in order to create a vessel systematization based on measured attributes. Finally, a general characterization is proposed and regional comparisons are provided. Pottery production and/or style consumption patterns in Laguna Blanca exhibit a variety non-exhausted by a single ceramic tradition. Stylistic patterns indicate contributions of manufacture traditions from various surrounding regions.